Optimización de la extracción de antioxidantes en subproducto de tamarindo (Tamarindus indica L.) - Paute Torres, Ana Belén (2016)
In the present work, the effect of the temperature and the sample / solvent ratio of the solid-liquid extracts on the compounds present in the tamarind (by-product) vein, using a 2k factorial design, was evaluated. After obtaining the optimum conditions, the extraction time of compounds was determined by extraction kinetics. In all the tests the content of polyphenols was measured using the Folin-Ciocalteu reagent and antioxidant activity for the methods: FRAP, ABTS and DPPH. The optimum conditions for total phenols were: 20 °C and sample / solvent ratio 1.67 g / 50 mL; For ABTS 60 °C and sample / solvent ratio 1.67 g / 50 mL; For FRAP 60 °C and sample / solvent ratio 5 g / 50 mL and DPPH 60 °C and sample / solvent ratio 1.67 g / 50 mL. The kinetics determined that the best time was 150 min for total phenols, and 120 min for ABTS and DPPH. In the DPPH method it was observed that the variables sample / solvent and temperature variables had a significant effect, whereas for total phenols, ABTS and FRAP, no variables had an effect.